Evaluation of the gingival condition and stress level of soldiers from the Brazilian Navy's Marine Corps during field training (Research, Society and Development, 2022)
The aim of this study was to evaluate the gingival condition and stress level of the military during field training. Thirty militaries were clinically evaluated at two times (1st and 10th - last day of the mission), by probing pocket depth (PPD), visible plaque index (VPI), and gingival bleeding index (GBI). After the clinical evaluation, the soldiers answered a stress questionnaire in both moments. The difference between the 1st and last day of the mission was verified by the Friedman and Wilcoxon tests and the correlation between stress x GBI and stress x VPI by the Spearman test (p0.05). There was no correlation between stress and gingival conditions. The military demonstrated a higher incidence of VPI and GBI at the end of the mission, especially in the posterior teeth. However, the stress was similar at the beginning and end of the mission.